Identification of novel bromodomain inhibitors of Trypanosoma cruzi bromodomain factor 2 ( Tc BDF2) using a fluorescence polarization-based high-throughput assay - Tavernelli, Luis Emilio (2024)
Bromodomains are structural folds present in all eukaryotic cells that bind to other proteins recognizing acetylated lysines. Most proteins with bromodomains are part of nuclear complexes that interact with acetylated histone residues and regulate DNA replication, transcription, and repair through chromatin structure remodeling. Bromodomain inhibitors are small molecules that bind to the hydrophobic pocket of bromodomains, interfering with the interaction with acetylated histones. Using a fluorescent probe, we have developed an assay to select inhibitors of the bromodomain factor 2 of Trypanosoma cruzi (TcBDF2) using fluorescence polarization. Initially, a library of 28,251 compounds was screened in an endpoint assay. The top 350-ranked compounds were further analyzed in a dose-response assay. From this analysis, seven compounds were obtained that had not been previously characterized as bromodomain inhibitors. Although these compounds did not exhibit significant trypanocidal activity, all showed bona fide interaction with TcBDF2 with dissociation constants between 1 and 3 µM validating these assays to search for bromodomain inhibitors.